Development In Nanomedicines Targeting Triple Negative Breast Cancer (Journal of Pharmaceutical Negative Results, 2023)
This review covers combination of all aspects from Triple negative breast cancer (TNBC) that were missed by some articles. Most of review study focus on epidemiology and management of disease but rarely on types of formulation used, so by proper awareness about disease and its management, the burden of disease and its ill effect can be reduced. TNBC is one of the most common malignancies in women and girls. It has several therapeutic benefits for treating TNBC. Small scale (nanometric), active and passive targeting, the potential to attach multiple centered on moieties, managed launch, and region-specific centered on are only some of the precise characteristics provided via nanotechnology. The conventional pharmacological therapy, modern-day control techniques, and novel healing modalities for TNBC are the main topics of this evaluate. The treatment of TNBC and breast cancers stem cells with a number of chemotherapeutic agents brought using nanocarriers, including polymeric nanoparticles/micelles, metal/inorganic NPs, and lipid-based totally NPs (Liposome, stable-lipid nanoparticles (SLNs), and nanostructured lipid vendors (NLCs), and so on., has been thoroughly discussed. Additionally, the use of nanomedicine for the remedy of TNBC, which includes the usage of CRISPR nanoparticles, as well as extra molecular goals such poly (ADP-ribose) polymerase (PARP) for in addition research, were discussed.